Diagnosis accuracy of Raman spectroscopy in colorectal cancer: A PRISMA-compliant systematic review and meta-analysis. Issue 34 (August 2019) - Zheng, Qiang; Kang, Weibiao; Chen, Changyu; Shi, Xinxin; Yang, Yang; Yu, Changjun
Abstract: Background: The clinical significance of Raman spectroscopy (RS) in colorectal cancer (CRC) patients still remains underestimated. We performed this meta-analysis to elucidate the diagnostic value in CRC patients. Methods: We systematically searched electronic databases for published articles. Fixed effect model and random effect model were used to calculate the pooled sensitivity, specificity, diagnostic accuracy, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR) and positive posttest probability (PPP) of CRC. Meta-regression and subgroup analysis were conducted to assess potential source of heterogeneity. We also used Egger linear regression tests to assess risk of publication bias. Results: Thirteen studies had been included (679 patients: 186 with premalignant lesions and 493 with malignant lesions). The pooled sensitivity, specificity, diagnostic accuracy, PLR, NLR, DOR and PPP for CRC screening using RS were 0.94 (0.92–0.96), 0.94 (0.88–0.97), 0.96 (0.94–0.98), 16.44 (7.80–34.63), 0.062 (0.043–0.090), 263.65 (99.03–701.96) and 86%, respectively. Conclusion: RS is a potentially useful tool for future CRC screening. It also offers potentially early detection for CRC patients.